(untitled) (Journal of history, 2026)
This article provides a comprehensive analysis of the practice of dynastic marriage alliances (heqin) as a key mechanism within the paradigm of relations between sedentary Chinese empires and the nomadic polities of the Great Steppe (Xiongnu, Wusun, Turks) from the Han period through to the early Turkic era. The source base comprises a corpus of official Chinese historical compilations (Weishu, Beishu, Zhoushu, Suishu, Tangshu), examined using historical-genetic, comparative-historical, and narrative methodological approaches. The study aims to elucidate the political nature, evolution, and specific characteristics of these marital unions as an instrument for establishing and sustaining "peaceful and kinship" relations. Analysis of the sources and scholarly literature demonstrates the continuity of this practice in interactions with various nomadic confederations. This permits the interpretation of heqin as a systemic component not merely of foreign policy, but of a comprehensive frontier strategy employed by Chinese empires, aimed at ensuring security and stability along the northern borders. Initially employed as a means of containing nomadic powers, the practice evolved during periods of Chinese fragmentation (e.g., the 6th century), when rival Chinese dynasties began to utilise alliances with the Turkic Khaganate to gain military-political advantage over one another. Consequently, dynastic marriages functioned as a fully-fledged element of security strategy, being closely integrated with military, economic, and administrative measures. This provides grounds for viewing them not as an ad hoc response, but as a deliberate, long-term instrument of statecraft.